Introduction: Following Marriage - Susan Frelich Appleton (Washington University Journal of Law & Policy, 2007)
Originally only a working title, “Following Marriage” proved attractive because of its openness. In the spirit of the classroom conversations that sparked this project, we wanted no limit on the different paths that the authors might take from their shared point of departure, marriage. We imagined as possible topics consideration of events that might take place after a given marriage (such as divorce or death), developments that have emerged beyond marriage (such as civil unions or domestic partnerships), conceptual changes that might follow as traditional marriage undergoes contemporary transformations (such as the deconstruction of gender or of sexual orientation, the decentering of sex, and resistance to marriage and the privilege that it entails), or an argument that makes the case for adhering to the traditional approach to marriage—to list just a few of the possibilities we first contemplated. The symposium includes a diverse collection of essays that show creativity, thoughtfulness, and a talent for challenging prevailing assumptions and norms. Despite the varied topics and analyses, each infuses “Following Marriage” with content that reveals why scholars and students alike find family law such a rich and provocative field, as briefly summarized below.
Keywords: Marriage; Families; Civil unions; Domestic relations; Children; Family law; Community parenting; Same-sex marriage -- Australia; Same-sex marriage; Gender discrimination